Impact of Technology on Auditing: Evidence in Developing Countries (المجلة الدولية للبحوث العلمية, 2024)
Developing countries face unique challenges in ensuring good governance and effective use of resources, which necessitates technology for auditing as traditional methods struggle to address them adequately. Auditor shortages and funding constraints make it difficult to effectively cover public and private entities; hence, most developing countries’ technology adoption is still in its infancy. In recent years, public entities and private organizations are increasingly using digital systems for financial transactions, creating a vast amount of electronic data that requires real-time monitoring. Technology has made companies focus on internal auditing to evaluate the effectiveness of internal controls in influencing performance and detecting errors. Internal auditing systems root out irregularities leading to poor decisions and enable companies to achieve their goals, and technology has made the process fast and reliable. Auditors can analyze huge volumes of structured and unstructured data in the company while accessing 100% of user data to eliminate fraud and inconsistencies. Internal audit is considered an important factor in business because it enables the business to stay on course by reporting the company’s financial performance. The purpose of this paper is to examine how Malaysia adopted technology and revolutionized internal auditing.